Prices of accommodation rental as functioning on the basis of a sharing economy in the capitals of cee states - Mach, Łukasz (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2020)
Housing rental from private resources, thanks to the growing popularity of a sharing economy, is becoming more and more common. The principles of market activities compliant with the assumptions of a sharing economy create new frameworks in the science of economics, simultaneously subjecting classical methods and tools of management to verification. Making use of new information technologies and peer-to-peer technology, which as part of the former, has facilitated using a sharing economy in the hotel industry, creating a new community in the rental of housing market – people providing services of short-term renting of private accommodation facilities. The conducted research presents one-day rental (of the Bed & Breakfast type) functioning in compliance with the principles of a sharing economy. Its parametrization was carried out in the area of the formation of prices and their distribution. The resources of B&B rental were examined in the capital cities of Central and Eastern Europe. For each city the average prices of rental were determined, as were the average prices of extra services provided within the business activity (i.e. mean service charges and mean charges for cleaning). Additionally, a comparative analysis was carried out regarding the pricing of average rental costs with a simultaneous study of the significance of the differences observed in them. The conducted research allowed defining the structure of the total price of rental, which is composed of the price of the rental displayed on the webpage including offers of B&B rental and additional charges, i.e. the service and the cleaning fees. It follows from the conducted research, among others, that about one-third of the offered housing rental resources did not charge fees for cleaning and that the mean total price of housing rental for all the capitals of European the post-communist states ranged between 50 and 60 euros per night. From the point of view of the mean total rental price, the most expensive cities are Tallinn and Bratislava, whereas the cheapest countries are Bulgaria and Romania. The mean total rental prices for the capitals of Bulgaria and Romania are considerably lower than in the other capital cities of European post-communist states
Argumenta Oeconomica, 2020, Nr 2 (45), s. 141-162
Keywords: sharing economy; real estate; accommodation rental; peer-economy; price level; Central and Eastern Europe